Analisa Penerapan Sistem Scada Pada Pengendalian Jaringan Tegangan Menengah 20 KV PT. PLN Area Payakumbuh - Heru Susanto; Novery Lysbetti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
In Indonesia, the population growth from year to year making greater electrical power requirements. The increasing need for electrical power is obviously increasing the need for power generation as well. It will also greatly affect the operating costs, particularly fuel costs are also getting bigger, so as to obtain electrical power quality and reliable yet economical needed an electric power system operation management was good.Aplication of SCADA systems on the electrical system will automatically increase the level of understanding of the dispatcher, the electrical systems and SCADA systems are applied to the electric power distribution network designed to monitor the activities kelistrikkan at each substation, so the condition of the electricity network can be monitored in real time. In addition to these functions with the SCADA system also serves to perform commands Remote control open /close an LBS (lose breaker sircuit), telsignal and telematering.Keywords: Electricity, SCADA